Analysis and Implications of the Impact of the Sex Industry and Anime Industry on Japan’s Foreign Trade - Xu, Yongdong (Asia Pacific Economic and Management Review, 2025)
Against the backdrop of intensifying globalisation and competition in cultural soft power, the impact of specific industries on a nation’s foreign trade has become increasingly complex and multifaceted. Japan, as the world’s third-largest economy, features two seemingly disparate yet equally compelling industries within its foreign trade structure—the sex industry and the anime industry—both playing indispensable roles. This paper aims to systematically analyse the direct and indirect impacts of these two industries on Japan’s foreign trade. The anime industry, as a core pillar of Japan’s cultural exports, generates substantial trade surpluses through copyright licensing, merchandise, tourism, and other avenues, significantly enhancing the nation’s image[¹]. Meanwhile, the sex industry, operating within a legal grey area, though difficult to quantify precisely in terms of direct exports, makes a significant implicit contribution to the trade balance. This is achieved by fostering related content industries such as adult videos and adult games, as well as attracting specific types of inbound tourism. This paper will delve into the economic logic, operational models, and socio-cultural controversies surrounding these two industries. Building upon this analysis, it will explore implications for other nations—particularly China—in developing cultural industries while balancing societal values with economic benefits.